2023
DOI: 10.3389/feart.2022.1116492
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of hydraulic fracture initiation and propagation for glutenite formations based on discrete element method

Abstract: The existence of gravels in the glutenite formations leads to the complex geometries of hydraulic fracturing propagation and difficult construction in fracturing engineering. To study the hydraulic fracturing propagation law of glutenite formations, this paper establishes a fracture propagation model for the heterogeneous glutenite formations based on discrete element method, and analyzes the effects of gravel content, particle size, distribution, horizontal stress difference, fracturing fluid viscosity and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It is necessary to combine the actual geological conditions during well factory fracturing. Research shows that in situ stress difference is the key factor affecting fracture morphology [42][43][44][45]. The hydraulic fractures' spacing, the quantity of hydraulic fracturing and the method of fracturing are important components of fracturing design, which have a great influence on the fracture propagation.…”
Section: Resultsmentioning
confidence: 99%
“…It is necessary to combine the actual geological conditions during well factory fracturing. Research shows that in situ stress difference is the key factor affecting fracture morphology [42][43][44][45]. The hydraulic fractures' spacing, the quantity of hydraulic fracturing and the method of fracturing are important components of fracturing design, which have a great influence on the fracture propagation.…”
Section: Resultsmentioning
confidence: 99%
“…The simulations indicated that the induced stress field was the main factor confining the fracture propagation, and increasing the fracture space and pumping rate promoted fracture propagation. To further understand the change in the stress field during the whole production period, the ABAQUS and Computer Modelling Group Ltd. (CMG) (Calgary, AB, Canada) simulator was introduced to analyze the induced stress and production change [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%